Magnetism in nitronyl nitroxide radicals and their ion radical salts - Sugano, T; Blundell, S; Pratt, F; Hayes, W; Uekusa, H; Ohashi, Y; Kurmoo, M; Day, P (1997)
We report the results of magnetization, susceptibility and muon spin rotation/relaxation (mu SR) measurements and crystal structure analyses of the organic neutral and ion radicals based on nitronyl nitroxide. Magneto-structural correlations in naphthyl and quinolyl nitronyl nitroxides, some of which exhibit ferromagnetic intermolecular interactions, are discussed in terms of intermolecular and interatomic contacts. The temperature dependence of the paramagnetic susuceptibility of sodium 2-sulfonatofuryl nitronyl nitroxide and 2-carboxyfuryl nitronyl nitroxide are interpreted in terms of a combination of ferromagnetic and antiferromagnetic interactions. Of the organic radicals exhibiting ferromagnetic intermolecular interactions, magnetic transitions in the zero-field muon spin relaxation are observed in l-naphthyl and p-cyanophenyl nitronyl nitroxide below 0.10 and 0.17 K, respectively.